Desempenho de sistema predial de água quente - Benedicto, Sergio Murilo de Oliveira (Universidade Federal de São Carlos, 2009)
In Hydraulic and Sanitary Building Systems there are nonconformance issues that can occur when user begins occupying and interacting with the building. Among other systems, the Hot Water Building System is responsible to offer to user important activities to human being such as bath and dish washing. The performance of the systems that constitute the housing buildings along its life is connected to the conditions of use for it was designed, to the execution of the construction according to the technical regulations, to the use of materials and components free of imperfections and to the programs and techniques of regular auditing and building maintenance. Even though the field of nonconformance is a subject not so explored in Brazil, it can be inferred as causes of nonconformance issues in the Hot Water Building System: technical regulations out-of-date, project mistakes, inadequate specifications, manufacture problems, execution errors, lack of maintenance or inadequate maintenance. This dissertation, based on the user's requirements as established by NBR 15575-1, objects the identification of performance requirements and criteria, to multistoried residential buildings. This theoretical study was applied to two multistoried residential buildings to find out probable s nonconformance.
Performance of hot water building system
Keywords: Construção civil; Sistemas prediais; Instalações hidráulicas e sanitárias; Sistema predial de água quente; Patologia da construção; Civil construction; Building systems; Hydraulic and sanitary building systems; Hot water building system; Building performance; Construction pathologies; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL